Evolution of free amino acids, biogenic amines and volatile compounds in fermented sausages inoculated with Lactiplantibacillus plantarum and Staphylococcus simulans - Xuefei Shao; Huhu Wang; Xiangyu Song; Mingyuan Huang; Jian Sun; Xinglian Xu (Food Science and Human Wellness)
Lactic acid bacteria and coagulase-negative staphylococci play an important role in the production of fermented sausages, such as inhibiting the growth of undesirable bacteria and antioxidant. In this study, the effects of inoculation with different starter cultures (Lactiplantibacillus plantarum HN108 and Staphylococcus simulans NJ209) on the free amino acids (FAAs), biogenic amines (BAs) and volatile compounds of fermented sausages were investigated using an amino acid analyzer, ultra performance liquid chromatography and gas chromatography-ion mobility spectrometry, respectively. The pH and carbonyl content of the inoculated group was significantly lower than those in the control group (P < 0.05). L. plantarum HN108 significantly reduced the content of FAAs and BAs in fermented sausage production (P < 0.05), while S. simulans NJ209 promoted the formation of FAAs (especially bitter amino acids) and exhibited slight BAs-reducing activity. In addition, L. plantarum HN108 promoted the formation of volatile compounds such as ketones, alcohols and alkenes in sausages. In conclusion, L. plantarum HN108 could contribute to reducing the content of putrescine and tyramine and forming the desirable flavor compounds in fermented sausages. Thus, L. plantarum HN108 is expected to be a starter culture that can improve the safety and flavor of fermented sausages.